2019
DOI: 10.1016/j.tmp.2019.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Managing a non-profit hospitality platform conversion: The case of Couchsurfing.com

Abstract: Couchsurfing (CS) was founded in 2003 as a non-profit for those interested in creating a common resource for world-wide hospitality exchange and low cost tourism. Built around a non-market communal sharing model, it became a for-profit in August 2011. Applying a discourse relational model approach, this study characterizes how competing discursive articulations over the conversion led to a discursive strategy of moral justification as management sought to retain its non-profit, alternative, democratic imaginar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Couchsurfing is a non-institutional travel way that has quickly grown worldwide in recent years (Luo and Zhang 2016). The primary missions of Couchsurfing are to help travelers get accessible accommodations, exchange information while traveling, and interact with locals (O’Regan and Choe 2019). Tourists are supposed to verify their identities on Couchsurfing websites and/or applications to assure their reliabilities to their potential peers (Decrop et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Couchsurfing is a non-institutional travel way that has quickly grown worldwide in recent years (Luo and Zhang 2016). The primary missions of Couchsurfing are to help travelers get accessible accommodations, exchange information while traveling, and interact with locals (O’Regan and Choe 2019). Tourists are supposed to verify their identities on Couchsurfing websites and/or applications to assure their reliabilities to their potential peers (Decrop et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…However, as we mentioned before, the limited literature about other forms of P2P accommodation enabled us only to compare the most common topics found between Couchsurfing and Airbnb. The data on Couchsurfing were based on the review article by Prayag and Ozanne (2018) and the WoS core collection articles (Uzunca and Borlenghi, 2019; O’Regan and Choe, 2019; Chen, 2018; Decrop et al , 2018; Chen, 2017; Luo and Zhang, 2016; Lampinen, 2016; Germann Molz, 2013; Rosen et al , 2011). As can be observed in Table III, seven common topics studied in the Couchsurfing literature were found.…”
Section: Most Common Topics Studied On Airbnb and Other Peer-to-peer Platformsmentioning
confidence: 99%
“…Referencing Table II, the authors found other commonly studied topics to be “business model” and “marketing experience”. We found literature related to the management of a non-profit hospitality platform based on Couchsurfing (O’Regan and Choe, 2019), but nothing else that could contribute to understanding important issues regarding the business models of other P2P accommodation platforms. As to “marketing experience”, we also found that this topic has not yet been covered in relation to other P2P accommodation platforms.…”
Section: Most Common Topics Studied On Airbnb and Other Peer-to-peer Platformsmentioning
confidence: 99%
“…Of the few published studies that have focused on NPOs, and marketing activities such as branding and rebranding, the research has focused on developed economies. Examples include the study of charity shops in Ireland and the United Kingdom (O'Callaghan, 2019; Broadbridge and Parson, 2003), and Peer-to-Peer (P2P) hospitality in Iceland (O'Regan and Choe, 2019). As noted above, and by definition, the study of Emerging economies has received lesser attention, and the fact that NPOs were not common in many of these regions, further limits the understanding of the sector with respect to variables such as branding and positioning.…”
Section: Research Literaturementioning
confidence: 99%